Zdrowotność oraz czas zarastania sęków po podkrzesaniu dębu - Mederski, Piotr; Brunka, Mariusz; Giefing, Dieter; Naparty, Kwiryn; Szczawiński, Dariusz (Leśne Prace Badawcze, 2019)
Artificial pruning of trees can improve wood quality as well as enhance timber value. Currently, pruning is quite common when veneer timber or plywood, is in demand. Cutting off branches, however, creates open wounds in the form of knots, which are exposed to infections. While the pruning of coniferous trees is well-studied, less research has been carried out on broadleaved trees. The objective of this work was to determine 1) if the artificial pruning of oak can lead to decaying knots, 2) if so, how big the decaying zone around the unsound knot is, and 3) how much time is needed for knot occlusion after artificial pruning. 13- and 16-year-old oak trees located in Northern Poland (Lidzbark Forest District) were used in this study and ten years after pruning, sample trees were selected in order to determine if the knots were sound and how many years it had taken for each knot to be overgrown. The results were compared with those of knots on trees caused by natural pruning. In total, 419 and 104 knots resulting from artificial and natural pruning, respectively, were analysed. It was found that 95% of the artificially pruned knots had very little decay showing an average of 1.13 cm of unsound knot zone. On the naturally pruned control trees, 98% of the knots were unsound with nearly double the amount of knot decay zone. Additionally, the artificially pruned knots needed less than five years to overgrow, while it took over eleven years to occlude the naturally pruned knots. Therefore, the artificial pruning of oak trees is recommended, even though a very small decay zone may appear on the knots, because it takes half the time for these artificial knots to be overgrown in comparison with unpruned trees.